Comparative life cycle energy and cost analysis of post-disaster temporary housings. (1st June 2016) - Atmaca, Adem; Atmaca, Nihat
Highlights: Life cycle energy and cost analysis of post disaster housings have been studied. Life cycle energy use of PH70 and CH20 are calculated to be 18.5 and 24.7 GJ/m 2 . The life cycle costs of PH70 and CH20 are calculated to be 919 and 1308 $/m 2 . PH have 25.1 and 29.7% lower life cycle energy and cost requirements respectively. Abstract: Temporary housings play an important role by providing people a habitable environment while the effects of a disaster are being fixed. In this paper, life cycle energy and cost analysis of two common types of post-disaster temporary housings constructed in Turkey has been studied. The aim of this study was to identify whether it is more convenient to use prefabricated (PH) or container housings (CH) in post-disaster reconstruction projects. Construction and operational energy requirements are calculated over 15 years using a comprehensive approach. The energy and financial requirements of the housings have been evaluated by considering four different base areas. The life cycle investment, operation, maintenance, service and end of life costs have been investigated by using the net present value technique. Life cycle primary energy consumption values of the most widely used prefabricated (PH70) and container (CH20) housings are calculated to be 18.5 and 24.7 GJ/m 2, respectively. The results show that operational phase was dominant over the housings 15-year lifetime. The life cycle cost of PH70 and CH20 are calculated to be 919 and 1308 $/m 2, respectively. It is found that increasing the total base area of the housings is an important cost-effective energy reduction measure. The results expressed that prefabricated housings have 25.1 and 29.7% lower life cycle energy and cost requirements respectively.